Outcomes of Liver Transplantation in Treated Portopulmonary Hypertension Patients With a Mean Pulmonary Arterial Pressure ≥35 mm Hg. Issue 12 (December 2020) - DuBrock, Hilary M.; Runo, James R.; Sadd, Corey J.; Burger, Charles D.; Cartin-Ceba, Rodrigo; Rosen, Charles B.; Taner, Timucin; Nyberg, Scott L.; Heimbach, Julie K.; Findlay, James Y.; Krowka, Michael J.
Abstract : Background: Portopulmonary hypertension (POPH), pulmonary arterial hypertension (PAH) that develops in the setting of portal hypertension, affects 5%–6% of patients with liver disease and is associated with significant morbidity and mortality. A mean pulmonary arterial pressure (mPAP) threshold of 35 mm Hg is used to stratify perioperative risk and liver transplant eligibility in treated POPH patients but does not take into account the specific factors that contribute to the pressure elevation. Methods: In this case series, we describe the characteristics and posttransplant outcomes of patients with treated POPH and an mPAP ≥35 mm Hg and pulmonary vascular resistance (PVR) <250 dynes-s-cm −5 at or just before liver transplantation (LT). We also describe the effect of PAH therapy on pulmonary hemodynamics in patients with POPH. Results: Sixteen patients were included. All patients were on PAH therapy at the time of LT. PAH therapy resulted in a decrease of mPAP (median 18.4%; interquartile range [IQR] 8.9%–27.0%) with a reduction in PVR (median 50.5%; IQR, 45.4%–70.7%), and an increase in both cardiac output (CO) (median 28.1%; IQR 5.7%–63.8%) and PAWP (median 50.0%; IQR 16.7%–108.3%) before LT. One year posttransplant survival was 69% (11/16); however, only 1 death was attributed to POPH. At 1-year posttransplant, 63.6% (7/11) of patients were weaned off all PAH therapy with clinical and echocardiographic resolution of POPH. Conclusions: In treated POPH patients with an mPAP ≥35 mm Hg and PVR < 250 dynes-s-cm −5 before LT, 1-year posttransplant survival was 69% and the majority of patients were able to discontinue PAH therapy.